Career adapt-ability scale -short form: Validation among early career stage of Chinese university graduates - Song, Chunze; Hashim, Shahabuddin Bin; Xu, Xinpeng; Ling, Hairong (Frontiers in Psychology, 2023)
The Career Adapt-Ability Scale (CAAS) is the favored method among researchers for measuring career adaptability. The 12-version of CAAS-SF, which was made by Maggiori, Rossier, and Savickas based on a change to CAAS, is slowly getting certified by different groups in different countries and regions. As samples for the validation of the scale in this study, 571 Chinese university graduates in the early stages of their professions were chosen. Principal component analysis and confirmatory factor analysis suggest that CAAS-SF and CAAS have very similar psychological measurement features and factor structures. And the internal consistency of each subscale and total scale are equivalent to or greater than that of the CAAS assessment. These findings indicate that the CAAS-SF is a valid and reliable instrument for evaluating China's career adaptability. In addition, limitations, issues for further research, and suggestions are emphasized.